Eschatologie alchimique chez jâbir ibn Hayyân - Pierre Lory (Université de Provence, 2000)
The corpus of texts attributed to the alchemist Jâbir ibn Hayyân, which was probably completed during the first half of the 1 Oth century AD, delivers several elements of an original eschatological extreme Shî'i doctrine. Jâbir does not give an opinion on the question of the succession of the Imams which divided the Shî'i movement at that time : according to his school of thought, the encounter with the Imam happens by means of gnostic knowledge, and especially through the discovery of the secrets of alchemy as a global universal science. The present article attempts to shed light upon new evidence on the basis of an analysis of the Kitâb al- Bayân. According to this text, the collective salvation of mankind from the prison of ignorance will happen with the help of the spreading of esoterical sciences. At the end of times, a messianic divine and human person called the Bayân will manifest the hidden dimensions of being and fulfill the destiny of the whole of mankind.